Asian American Spring Festival 1989 Flyer 02 (SJSU Asian American Studies Department, 2024)
Asian American Spring Festival logo. The logo has a man playing the Taiko, with an in pink. Above the logo is the text "9th Annual." Under the logo is the text "San Jose State University 1989." Designers the logo are Jason Leong & Al Perez, Jr.